Resilience And Quality of Life of Hemodialysis Patients: Literature Study - Moh Saefudin; Dwi Retno Sulistyaningsih; Ahmad Ikhlasul Amal; Nopi Nur Khasanah (Universitas Islam Negeri Alauddin Makassar, 2025)
Resilience is a significant factor closely associated with the quality of life and well-being of patients undergoing haemodialysis. Resilience serves as a protective factor that can enhance patients' adaptive capabilities and their skills in implementing positive coping strategies. Research on the relationship between resilience and quality of life in haemodialysis patients is still limited and has not been extensively studied. This study aims to explore the interconnection between resilience and quality of life in haemodialysis patients. A search for article data sources was conducted by applying inclusion and exclusion criteria in accordance with the PRISMA format through various databases such as Emerald, PubMED, and ProQuest, as well as e-resources from the National Library. Additionally, searches were performed on article sites such as ResearchGate, Science Direct, and Google Scholar for the period 2019-2024. The keywords utilised included: “Resilience” or “Resiliency” or “Resilient” and “quality of life” and “Haemodialysis”. Data were extracted by documenting the author's name, year, country, objective, respondents, design, findings, and implications. The study design included literature reviews in the form of abstracts or full texts from research journals. The quality of the research was evaluated using the PRISMA literature search diagram. From 13 reviewed journals, the analysis indicated that 9 articles suggested a relationship between resilience and the quality of life of haemodialysis patients, whereas 1 article reported no relationship, and 3 other articles highlighted additional factors related to resilience in haemodialysis patients. Enhancing resilience should be a focus in the care of haemodialysis patients to support the achievement of better quality of life. Indicators related to resilience are factors that influence the quality of life of haemodialysis patients. The role of resilience on an individual level requires further investigation within the context of quality of life variables in haemodialysis patients. Keywords: Factors related, hemodialysis, quality of life, resilience